NAVIGATING ACADEMIC–WORK ROLE CONFLICT: COPING STRATEGIES, STRESSORS, AND SUPPORT SYSTEMS AMONG WORKING UNIVERSITY STUDENTS - Lina Mu’arrofatul A’la; Heri Saptadi Ismanto; Agus Setiawan (EDUCATIONE, 2026)
Working university students may experience academic–work role conflict when study requirements and paid employment compete for limited time and energy. This bounded qualitative case study examined the stressors experienced by student employees, the coping responses they used, and the contribution of social and organizational resources. The case comprised two university students (KN and RA) employed in a service-sector coffee shop in Semarang, Indonesia, and the workplace owner (OW) as a supporting informant. Data were generated through interviews, observation, and documentation and analyzed through an interactive process of data condensation, display, and conclusion verification. Five interrelated stressor clusters were identified: schedule and time conflict, academic demands, dual-role fatigue, family expectations, and self-imposed pressure concerning study completion. The students used problem-focused coping through prioritization and solution seeking and emotion-focused coping through rest, emotional regulation, interpersonal disclosure, and spiritual practice. Support seeking was distinguished from received support; peer encouragement and employer-provided schedule flexibility functioned as external protective resources. The case suggests that adaptation is shaped by interactions among stress appraisal, coping behavior, and contextual resources. Higher-education counseling should therefore combine individual coping development with early overload identification, flexible academic advising, peer support, and context-sensitive coordination with employers. Comparative, longitudinal, and mixed-method research is needed to test the transferability of this case-derived framework.